2016
DOI: 10.1186/s40064-016-3582-6
|View full text |Cite
|
Sign up to set email alerts
|

Features of omental adipose tissue in endometrial cancer patients with ‘standard’ or ‘metabolically healthy’ obesity: associations with tumor process characteristics

Abstract: PurposeAdipose tissue products may contribute to endometrial cancer (EC) initiation and further growth that encourages the analysis of this issue in patients with different obesity phenotypes.Methods/patientsOmental fat depot characteristics were studied in EC patients (n = 57) with “standard” (SO) or “metabolically healthy” (MHO) obesity. Collected omental samples were evaluated by immunohistochemistry /IHC/ for brown fat marker UCP1, CYP19 (aromatase) and macrophage infiltration markers (CD68, CD163, crown-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
1
3
0
1
Order By: Relevance
“…Interestingly, it has recently been reported that breast WAT from Black women, who have worse prognosis with breast cancer, have higher density of CLS-B than their non-Black counterparts (22). The probability that WAT inflammation helps to explain the obesity-inflammation-carcinogenesis axis is further supported by observations showing the occurrence of CLS in adipose tissue associated with other malignancies, including oral squamous cell carcinoma of the tongue (23), endometrial cancer (24), and in the report of liver macrophages, identified as Kupffer cells, forming CLS with lipidladen hepatocytes in NAFLD, a disorder now considered to be a precursor for hepatocellular cancer (14,25).…”
Section: Articles By Iyengar Et Al Published In This Issue Cancer Prsupporting
confidence: 52%
“…Interestingly, it has recently been reported that breast WAT from Black women, who have worse prognosis with breast cancer, have higher density of CLS-B than their non-Black counterparts (22). The probability that WAT inflammation helps to explain the obesity-inflammation-carcinogenesis axis is further supported by observations showing the occurrence of CLS in adipose tissue associated with other malignancies, including oral squamous cell carcinoma of the tongue (23), endometrial cancer (24), and in the report of liver macrophages, identified as Kupffer cells, forming CLS with lipidladen hepatocytes in NAFLD, a disorder now considered to be a precursor for hepatocellular cancer (14,25).…”
Section: Articles By Iyengar Et Al Published In This Issue Cancer Prsupporting
confidence: 52%
“…Peculiar histological structures, known as crown-like structures, characterized by dead or dying adipocytes surrounded by macrophages, are increased in the adipose tissue linked to obesity, and have been involved in the activation of nuclear factor-kB and the generation of a proinflammatory microenvironment. Concomitantly, they have been reported to play a role in the initiation and progression of endometrial cancer [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…CLS are associated with free fatty acid (FFA) release, NF-κB activation and the generation of a proinflammatory microenvironment [ 106 ]. They are best characterized for their role in the initiation and progression of breast cancer [ 106 ] but they are also reported to play a role in endometrial cancer [ 107 ], prostate cancer [ 108 ] and non-alcoholic steatohepatitis (NASH)—a major risk factor for HCC [ 109 ]. In breast adipose tissue CLS are not only associated with inflammation but they also drive aromatase activity resulting in an increased ratio of estrogen:androgen in blood and local tissues [ 110 ].…”
Section: Mechanisms Linking Adipose Tissue To the Metastatic Cascamentioning
confidence: 99%